Reading in Spanish and Italian: Effects of Age of Acquisition in Transparent Orthographies?. Issue 9 (September 2014) - Davies, Rob; Wilson, Maximiliano; Cuetos, Fernando; Burani, Cristina
Despite the similar transparency of their orthographies, reading in Italian has been found to be affected by frequency but not age of acquisition (AoA) [Barca, L., Burani, C., & Arduino, L. S. (2002). Word naming times and psycholinguistic norms for Italian nouns. Behaviour Research Methods, Instruments and Computers, 34, 424–434] while reading in Spanish is affected by AoA but not frequency [Cuetos, F., & Barbón, A. (2006). Word naming in Spanish. European Journal of Cognitive Psychology, 18, 415–436]. We examined this cross-linguistic difference, firstly, through a reanalysis of the Italian and Spanish reading latencies. After eliminating several between-experiment differences, we replicated the AoA effect in Spanish but not in Italian and the frequency effect in Italian but not in Spanish. The cross-linguistic comparison could not equate stimulus imageability; therefore, secondly, we compared the Italian reading latencies with new Spanish reading latencies for imageability-matched words. We found frequency effects but neither an AoA effect nor a language by AoA interaction. We argue that the previously reported cross-linguistic difference in the AoA effect resulted from a between-study difference in stimulus imageability. More imageable words induced more semantic involvement in reading, yielding an AoA effect in Spanish.